Residual stress, thermomechanics & infrared imaging, hybrid techniques and inverse problems. proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics. Volume 9 : ([2016]) - Unknown
No abstract available